Evaluation of Relationship between Health Literacy and Illness Perception in Patients with Multiple Sclerosis in Iran - Fariba Abdollahi; Seyede Soghra Taher Harikandeie; Leila Dehghankar; Zahra Tayebi Myaneh; Simin Zarrabadi Pour (Golestan University of Medical Sciences, 2022)
Background: Inadequate health literacy has negative effects on physical and mental performance, medication adherence, self-care behaviors and quality of life . The impact of health literacy on different aspects of illness perception in patients with Multiple Sclerosis (MS) is not clear. Therefore, the present study aimed to determine relationship between health literacy and illness perception in patients with MS. Methods: This was a correlational study on 100 patients with MS who had been referred to neurology clinic of Abu Ali Sina Hospital in Qazvin (Iran) in 2017-2018. The subjects were enrolled via convenience sampling. A demographic information questionnaire, the Newest Vital Sign (NVS) health literacy instrument, and the brief illness perception questionnaire (BIPQ) were used to collect data. The data were analyzed in SPSS (version 22) using descriptive statistics, the Pearson correlation coefficient, and linear regression model. Results: Adequate health literacy  level was found in 11% of patients; 26% had a possibility of limited health literacy and 63% had a high likelihood of limited health literacy. The mean illness perception score was 35.53±1.31 (moderate). There was no significant relationship between health literacy and the mean score of illness perception (r=-0.014, P=0.894). However, there was a significant relationship between perception and recognition of present illness, as a subscale of illness perception with health literacy (r=0.243, P=0.015). Variables in the multi-variate predictive model accounted for 37.6 % of the total variance in heath literacy.  Duration of illness perception significantly predict health literacy (B=0.052, P=0.035). Moreover, the only predictor of illness perception in patients with MS was income level (B=87.87, P=0.05), which explained 35.7% of the illness perception changes. Conclusion: Based on the results, illness perception is significantly associated with health literacy. Therefore, it is necessary to promote health literacy in order to improve understanding the nature and consequences of the disease and conduct further research on the relationship between health literacy and illness perception among patients with MS.